ANÁLISE MOLECULAR DE RESISTÊNCIA A QUINOLONAS E FLUORQUINOLONAS EM Escherichia coli UROPATOGÊNICA - Freitas, Denis Leandro de (2013)
The urinary tract infections (UTI) have high incidence in the population, mainly affecting women, the elderly and pregnant women. In most cases an UTI is caused by Enterobacteriaceae, especially Escherichia coli. The main antimicrobials used in the treatment of UTIs, are the quinolones and fluoroquinolones. Since its discovery in the 60s, such antimicrobials were improved and increasing its spectrum of activity, but also the micro-organisms has evolved to develop resistance to these drugs. The resistance comes down to two mechanisms: changes in targets of quinolones or decreased concentration of the drug within the cell. Quinolones are antimicrobial agents that target two enzymes involved in transcription and replication of bacterial DNA, DNA Gyrase, consisting of two subunits GyrA and two GyrB products of the genes gyrA and gyrB respectively and Topoisomerase IV, also composed of two ParC and two ParE subunits, encoded from genes parC and parE. Mutations in these genes can confer high-level resistance to these antimicrobials. Other mechanisms involve genes carried in plasmids such as qnr's, responsible for the production of proteins that protect the target enzymes of quinolones. The gene aac (6 ')-Ib-cr also present in plasmids can alter the chemical structure of certain fluoroquinolones interfering efficiency. The association of resistance to quinolones and β-lactams due to the presence of Extended Spectrum β-lactamases (ESBL) has been widely reported in the literature. The main objective of this study was to evaluate the patterns of resistance to quinolones and fluoroquinolones in 55 samples of uropathogenic E. coli collected in Curitiba, PR, Brazil. The resistance to nalidixic acid, norfloxacin, ciprofloxacin and ofloxacin was observed in 69.1% of the samples. Molecular analysis of the resistant strains showed mutations in gyrA (codons 83 and 87) and parC (codon 80). Also investigated was the presence of genes qnr's and aac (6 ')-Ib-cr and their association with ESBLs. Two of the 55 samples were positive for aac (6 ')-Ib-cr. The presence of this gene in Brazil was first reported in 2012 in Belo Horizonte, MG. No samples were positive for the qnr's genes. These results show a high incidence of resistance to quinolones and the ability to horizontally spread of acquired resistance between the bacterial strains.